Promising antimalarial hits from phenotypic screens: a review of recently-described multi-stage actives and their modes of action - Luo, Annie-Peiyuan; Giannangelo, Carlo; Siddiqui, Ghizal; Creek, Darren J. (Frontiers in Cellular and Infection Microbiology, 2023)
Over the last two decades, global malaria cases caused by Plasmodium falciparum have declined due to the implementation of effective treatments and the use of insecticides. However, the COVID-19 pandemic caused major disruption in the timely delivery of medical goods and diverted public health resources, impairing malaria control. The emergence of resistance to all existing frontline antimalarials underpins an urgent need for new antimalarials with novel mechanisms of action. Furthermore, the need to reduce malaria transmission and/or prevent malaria infection has shifted the focus of antimalarial research towards the discovery of compounds that act beyond the symptomatic blood stage and also impact other parasite life cycle stages. Phenotypic screening has been responsible for the majority of new antimalarial lead compounds discovered over the past 10 years. This review describes recently reported novel antimalarial hits that target multiple parasite stages and were discovered by phenotypic screening during the COVID-19 pandemic. Their modes of action and targets in blood stage parasites are also discussed.